Synthesis And Interaction Mechanism Of Zwitterionic Adsorbent Coating For Cationic And Anionic Dyes Removal - Azha, Syahida Farhan (2019)
Adsorption is an extensively used technique in color wastewater treatment since the process is practical in operation, economical, efficient and flexible in adsorbent design. However, the occurrence of fine powdery or flakes adsorbents with nano-sized, irregular shape and unstable density will cause complexity once applying in continuous flow system. Fast loss of adsorbent, leaching and obstruction phenomena in column among the problems created. Thus, this research focused on development of an adsorbent based coating with zwitterionic functionality for the removal of cationic and anionic dyes from aqueous solution. The adsorbent coating was prepared through a facile method based on the combined used of additive (bentonite clay), surfactant (cationic polyelectrolyte, EPIDMA), solvent (distilled water), and binder (acrylic polymer emulsion, APE), which then coated on cotton cloth as a substrate. The optimum formulation ratio was confirmed as 1:2:4, reciprocated to swelled bentonite (g): APE (g): EPIDMA (wt. %). The novel zwitterionic adsorbent coating which then referred as ZwitAd was characterized and analysed to ascertain its chemical and physical properties. The ZwitAd exhibited significant performance in removal efficiency and adsorption capacity for both working dyes (either in single or simultaneous adsorption) together with good coating strength, chemical and thermal stability. The mechanism of dyes adsorption can be ascribed via electrostatic attractions between amphoteric adsorbent surfaces (positive and negative charges) with the sulfonate anionic −SO3 ¯ group of Acid Red 1 (AR1) dyes and (=NH)+ groups of Brilliant Green (BG) dye. Another interaction may involved hydrophobic and hydrogen bonding. The effect of initial dyes concentration (10 ppm-250 ppm), adsorbent dosage (0.1 g- 0.5 g), initial pH (2 – 12), ionic strength (1 g/L - 5 g/L), temperature (30-70 °C), effect of binary and tertiary dyes, adsorption on other types of pollutants and reusability study were investigated in precise. In addition, the equilibrium isotherms, kinetics, thermodynamics and mechanism studies were also evaluated. The result showed increasing contact time and dye concentration led to a rapid increment in the adsorption capacities of ZwitAd especially for the elimination of AR 1 dye. Variation in initial dye concentration from 50 mg/L to 250 mg/L, gave a corresponding increase in adsorption capacities from 33.33 mg/g to 74.50 mg/g for AR 1 dye and 34.83 mg/g to 183.01 mg/g for BG dye. Besides, ZwitAd was excellent in relatively wide pH range from 2 to 12. Maximum 10 consecutive cycles of adsorptiondesorption of BG dye was achieved by applying thermal regeneration study. The obtained adsorption data were assessed based on equilibrium adsorption isotherms and best described by Freundlish isotherm for both dyes. The model connotes that the multilayer adsorption on ZwitAd heterogeneous surfaces. The kinetic model revealed that pseudo- first-order was in better agreement with AR 1 and pseudo-second-order for BG dye. Thermodynamic studies also revealed that adsorption was spontaneous and endothermic process. The current study discovered the potential of ZwitAd as a feasible and practical coating adsorbent for future wastewater treatment technology.